Emerging New Treatments for Colon Cancer - Adedayo, Sheu Ibrahim; Sonnenberg-Riethmacher, Eva (Current Medicinal Chemistry, 2025)
Colorectal cancer includes cancer of the rectum and colon. It is the primary cause of cancer-related deaths among men under 50 years of age. In 2022, over 1.9 million cases of CRC were reported, resulting in approximately 904,000 deaths worldwide. Factors like smoking, alcohol consumption, obesity, familial history, and inflammation significantly contribute to the risk of CRC development. Additionally, bacterial infections from organisms like <span class=
Keywords: probiotics